1972
DOI: 10.1136/hrt.34.6.611
|View full text |Cite
|
Sign up to set email alerts
|

Blood coagulation changes at high altitude predisposing to pulmonary hypertension.

Abstract: Blood coagulation studies were carried out in 38 Indian soldiers who were resident at altitudes between I2,000 and i8,0oo feet for 2 years. Compared with I6 sea-level controls, 6 of these 38 subjects who had developed pulmonary hypertension during their stay at high altitude showed a significant increase ofplasmafibrinogen,fibrinolytic activity, platelet adhesiveness, plateletfactor 3, factor V, and factor VIII. In the remaining 32 subjects who did not develop pulmonary hypertension there was a significant inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 14 publications
2
44
1
Order By: Relevance
“…An additional 8 days at that altitude produced an increase to 7% below control levels. Similarly Chatterji et al (1982) found a 12%-26% fall in platelet counts after 48-72 h at 3200 m and 3771 m. Conversely Singh and Chohan (1972a) showed a significant rise in platelet numbers in 32 Indian soldiers ascending to between 3600 m and 5200 m. Sharma (1986) failed to demonstrate a significant difference in platelet numbers when 50 soldiers were moved from low altitude to 3650 m. However, in an earlier study he had reported a slight but significant increase in platelet numbers in well subjects, the reverse being seen in those with symptoms suggestive of acute mountain sickness (AMS) (Sharma 1980). All these studies used manual methods for platelet enumeration.…”
Section: Introductionmentioning
confidence: 93%
“…An additional 8 days at that altitude produced an increase to 7% below control levels. Similarly Chatterji et al (1982) found a 12%-26% fall in platelet counts after 48-72 h at 3200 m and 3771 m. Conversely Singh and Chohan (1972a) showed a significant rise in platelet numbers in 32 Indian soldiers ascending to between 3600 m and 5200 m. Sharma (1986) failed to demonstrate a significant difference in platelet numbers when 50 soldiers were moved from low altitude to 3650 m. However, in an earlier study he had reported a slight but significant increase in platelet numbers in well subjects, the reverse being seen in those with symptoms suggestive of acute mountain sickness (AMS) (Sharma 1980). All these studies used manual methods for platelet enumeration.…”
Section: Introductionmentioning
confidence: 93%
“…[1][2][3][4][5] In the case of highaltitude hypoxic exposure, both venous as well as arterial thrombotic events can occur, which include pulmonary thromboembolism, cerebral venous thrombosis, portal vein thrombosis, aortic thrombosis, stroke, and transient ischemic attack. [6][7][8][9] At extreme altitude, adverse environmental conditions including hypobaric hypoxia and cold may facilitate the development of the corresponding prothrombotic phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…3 Another study described changes in the coagulation factors suggesting an activation of the coagulation cascade and associated endothelial cell damage. 4 Anand et al reported a 30 times higher risk of spontaneous vascular thrombosis on long-term stay at high altitude in Indian soldiers.…”
Section: Discussionmentioning
confidence: 99%